Long Non-coding RNA HOTAIR in Central Nervous System Disorders: New Insights in Pathogenesis, Diagnosis, and Therapeutic Potential - Wang, Jialu; Zhao, Jiuhan; Hu, Pan; Gao, Lianbo; Tian, Shen; He, Zhenwei (Frontiers in Molecular Neuroscience, 2022)
Central nervous system (CNS) disorders, such as ischemic stroke, neurodegenerative diseases, multiple sclerosis, traumatic brain injury, and corresponding neuropathological changes, often lead to death or long-term disability. Long non-coding RNA (lncRNA) is a class of non-coding RNA with a transcription length over 200 nt and transcriptional regulation. lncRNA is extensively involved in physiological and pathological processes through epigenetic, transcription, and post-transcriptional regulation. Further, dysregulated lncRNA is closely related to the occurrence and development of human diseases, including CNS disorders. HOX Transcript antisense RNA (HOTAIR) is the first discovered lncRNA with trans-transcriptional regulation. Recent studies have shown that HOTAIR may participate in the regulation of the occurrence and development of CNS disorders. In addition, HOTAIR has the potential to become a new biomarker for the diagnosis and prognosis assessment of CNS disorders and even provide a new therapeutic target for CNS disorders. Here, we reviewed the research results of HOTAIR in CNS disorders to provide new insights into the pathogenesis, diagnostic value, and therapeutic target potential of HOTAIR in human CNS disorders.